Hubungan Pola Makan dan Aktivitas Fisik dengan Penyakit Rheumatoid Arthritis (reumatik) Pada Lansia Di Wilayah Kerja Puskesmas Cijagang Cianjur 2022 - Ani Cahyati; Siti Kamillah; Saiful Gunardi (Lembaga Pengembangan Kinerja Dosen, 2023)
Background: rheumatoid arthritis (reumatic) is the body's immune system that fails to distinguish its own tissue from foreign bodies, especially synovial tissue. Diet is the amount of food consumed by a person or group of people, while physical activity is body movement caused by the work of skeletal muscles and results in energy expenditure and energy (calorie burning). Purpose: to determine the relationship between diet and the incidence of rheumatoid arthritis (reumatic) in the elderly, to determine the relationship between physical activity and the incidence of rheumatoid arthritis (reumatic) in the elderly. . Method: this type of research is quantitative with a cross-sectional research design. With a sample of 40 respondents. Results: There were 25 (62.5%) unhealthy eating habits and a p value of 0.002, so it could be concluded that there was a relationship between diet and the occurrence of rheumatoid arthritis (rheumatism), and 27 (67.5%) light physical activity and a p value of 0.002. then it can be decided that there is a relationship between physical activity and the occurrence of rheumatoid arthritis (reumatic). conclusion: there is a relationship between diet and physical activity with the occurrence of rheumatoid arthritis (reumatic) in the elderly in the working area of ​​the Cijagang Health Center with a p value of 0.002.